Activity of heme metabolism enzymes in the kidneys under different nutrient supplies. - Гриненьків, Зоряна; Voloshchuk, Oksana (My University, 2021)
Today, the study of the effect of unbalanced nutrition on metabolic processes in the body remains relevant. The kidneys are among the most metabolically active organs, rich in mitochondria. Disruption of the energy supply processes in mitochondria leads to tubular dysfunction, which is considered to be one of the main causes of the emergence and progression of many kidney diseases. It is known that the kidneys intensively produce ATP, which is necessary to ensure biosynthetic processes, the release of end products of metabolism, reabsorption, maintenance of electrolyte and water-salt balance. Therefore, the question of the mechanisms of energy homeostasis disturbance, which may result in changes in the functional activity of the kidneys, under conditions of nutritional imbalance remains open. Our work aims to study the activity of key enzymes of heme metabolism in the mitochondrial fraction of rat kidneys under low-protein, high-sucrose, low-protein/high-sucrose diets.
Keywords: нутрієнти; мітохондрії; низькопротеїновий раціон